Chemical constituents from Vellozia graminifolia (Velloziaceae) - Branco,Alexsandro (2004)
From the hexane and ethyl acetate extracts obtained from stems, roots and leaf sheaths of Vellozia graminifolia, a mixture of linear hydrocarbons, a mixture of pentacyclic triterpenes, five monoisoprenylated flavonoids and one labdane diterpene, (-)-ent-3beta-hydroxy-8(17)-labden-15-oic acid, were isolated. The linear hydrocarbons and minor triterpenes were identified in their corresponding mixtures by High Resolution Gas Chromatography (HRGC) and HRGC coupled to mass spectrometry. The major pentacyclic triterpenes and the diterpene were characterized by spectral data, including 2D NMR experiments, and chemical transformations.